2022
DOI: 10.7554/elife.83299
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic flux-signaling controls mouse embryo mesoderm development

Abstract: How cellular metabolic state impacts cellular programs is a fundamental, unresolved question. Here we investigated how glycolytic flux impacts embryonic development, using presomitic mesoderm (PSM) patterning as the experimental model. First, we identified fructose 1,6-bisphosphate (FBP) as an in vivo sentinel metabolite that mirrors glycolytic flux within PSM cells of post-implantation mouse embryos. We found that medium-supplementation with FBP, but not with other glycolytic metabolites, such as fructose 6-p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 87 publications
3
41
1
Order By: Relevance
“…Increasing glucose led to a slower segmentation clock (Fig. 1C), which we also observed when fructose 1,6-bisphosphate (FBP), a glycolytic sentinel metabolite [6, 27], was supplemented to the medium (Fig. 1D).…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…Increasing glucose led to a slower segmentation clock (Fig. 1C), which we also observed when fructose 1,6-bisphosphate (FBP), a glycolytic sentinel metabolite [6, 27], was supplemented to the medium (Fig. 1D).…”
Section: Resultssupporting
confidence: 56%
“…We limited our analysis to the tailbud region, where the clock period phenotype is most apparent. Combined with the dataset from our previous study [6], this analysis revealed 617 flux-responsive differentially expressed genes (DEGs) that were either upregulated (Cluster (C) 1 and C3) or downregulated (C2, C4, and C5) by increasing glycolytic flux (Fig. 2A, Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, in mouse embryo explants glycolysis was reported to negatively regulate WNT signalling. 38,45 Although the authors suggested that the discrepancy could be rooted in short-term negative 38 versus long-term positive regulation 34 , our data show that -at the same time-point -higher glycolytic activity is positively associated with expression of WNTs and their targets. Our discovery that the FGF/WNT/glycolysis connection is conserved in the scalable and tractable stembryos presents an exciting opportunity to unravel the intricate spatiotemporal dynamics of feedback.…”
Section: Discussioncontrasting
confidence: 59%